(untitled) - Danilenko, Alexander (Washington DC., 2010)
The report was prepared by a Bank team comprised of Alexander Danilenko, Eric Dickson and Michael Jacobsen, supported by AECOM International Development (Surendra Bhatta, Rachel MacCleery and Hoai Huynh) and Global Water Intelligence (Ankit Patel). This report is structured as follows: Chapter 1 provides an overview of the role that climate change will have on urban water utilities and highlights the often competing priorities that water managers are faced with in developing countries; Chapter 2 describes the relationship between climate change and water resources as they influence water service provision; Chapter 3 presents a framework for analysis of vulnerability and adaptive capacity of water providers; Chapters 4 presents a framework for adaptation actions. Annexes contain detailed graphs and statistics taken from the international workshop held in Madrid, Spain in January of 2009 and utility specific case studies which are highlighted throughout the report.
Keywords: Climatic changes,Water supply,Water utilities,Biến đổi khí hậu,Cung cấp nước